The perceived influence of remote working on specific human resource management outcomes during the COVID-19 pandemic - Musawenkosi D. Saurombe; Simone S. Rayners; Kedibone A. Mokgobu; Keketso Manka (SA Journal of Human Resource Management, 2022)
Orientation: Remote work recently gained traction globally due to the coronavirus disease 2019 (COVID-19) pandemic, however, not all companies promptly adapted to this.